Implementasi Pembelajaran Sejarah Berbasis HOTS dalam Mengembangkan Kemampuan Analisis Historis Siswa - Nadya Anisa Iffa; Ronadia Ronadia; M. Riski Hidayatullah; Syarifuddin Syukur; Rani Oktapiani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study investigates the implementation of history learning based on Higher Order Thinking Skills (HOTS) in developing students' analytical history skills. This research is motivated by the dominance of conventional teaching focused on lectures that emphasize memorization of facts rather than critical and analytical thinking. The study aims to describe how HOTS-based strategies are implemented in history classes and to analyze their impact on students' analytical skills. This research uses a qualitative descriptive methodology. Data were collected through classroom observations, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that before the implementation of HOTS, students' responses were mostly descriptive and limited to recalling factual information. After the implementation of HOTS-based learning through the use of analytical questions, historical case studies, source analysis, and structured group discussions, students showed significant improvement in explaining cause-and-effect relationships, evaluating historical evidence, and building logical arguments. Students became more active in discussions and demonstrated a deeper conceptual understanding than mere memorization. However, several challenges were identified, including students' limited experience in critical thinking, time constraints, and the need for teachers to be better prepared in designing HOTS-oriented learning instruments. Overall, this study concludes that HOTS-based history learning effectively improves students' analytical history skills and shifts the learning orientation from lower-order thinking to higher cognitive engagement. This approach pedagogically contributes to fostering a critical, reflective, and contextual understanding of history that is relevant to the demands of 21st-century education.